The thyroid status of a conditionally healthy adult population of Prydniprovia - Arzhanov, I. Y.; Buniatov, M. R.; UshakovаG. A. (Regulatory Mechanisms in Biosystems, 2017)
Pathologies of the thyroid gland are one of the most common diseases in endocrinology today. Hormones of the thyroid gland carry out hormonal regulation of the cell cycle, the physiological and post-traumatic repair of cells. The hormones of the thyroid gland secrete and enhance the oxidative processes and control the heat production, which can affect the mental state and the ability of the body to adapt to adverse environmental factors. In the case of a lack or almost complete absence of thyroid hormones, normal development and function of any functional system in the body is not possible. In the context of an increase in the incidence of thyroid gland pathology inUkraine, this article presents an analysis of the thyroid status of the conditionally healthy population of Prydniprovia, related to age and gender. For the study, 120 patients of both sexes aged between 20 to 70 were selected. All patients were divided into 3 age groups of 40 people. Each age group was divided into 2 subgroups – male and female, with 20 people in each subgroup. Patients who, in the past and during the experiment, had no cases of thyroid gland disease were selected for accurate and reliable results. The study of thyroid status of the population showed that most of the adult and healthy population of Prydniprovia was not severely affected. All indicators were included in the age and gender limits of the norm, which are established by the preanalytical requirements of the independent laboratory Invitro (Dnipro,Ukraine). In women aged 50–70 years, there is an increased risk of hypothyroidism, which is confirmed by low levels of free thyroxine and triiodothyronine in the blood against the background of increased thyroid stimulating hormone and thyroglobulin levels. In the adult, conditionally healthy population of the Dnipro region aged between 20–70 years, the following correlation relations were observed between thyroid stimulating and thyroid hormones: at a younger age for men, the relationship between TSH and fT4 was –0.97, for TSH and fT3 –0.96, women also had a negative interdependence between these hormones (–0.95 and -0.98 respectively). The age of the men who underwent the test did not change this dependence but in women after 50 years, the Pearson correlation coefficient decreased between the studied hormones TTG and fT4 and fТ3 to –0.94 and –0.93, respectively. Indicators of total thyroxine and total triiodothyronine in the blood serum are not indicative for determining the risk of hypothyroidism.